Traumatic injury in female Drosophila melanogaster affects the development and induces behavioral abnormalities in the offspring - Ved Chauhan; Abha Chauhan (Behavioral and Brain Functions, 2019)
Abstract Traumatic injury (TI) during pregnancy increases the risk for developing neurological disorders in the infants. These disorders are a major concern for the well-being of children born after TI during pregnancy. TI during pregnancy may result in preterm labor and delivery, abruptio placentae, and/or fetomaternal hemorrhage. Drosophila melanogaster (fruit fly) is a widely used model to study brain and behavioral disorders in humans. In this study, we analyzed the effects of TI to female fruit flies on the development timing of larvae, social interaction and the behavior of offspring flies. TI to the female flies was found to affect the development of larvae and the behavior of offspring flies. There was a significant increase in the length of larvae delivered by traumatically injured maternal flies as compared to larvae from control maternal flies (without TI). The pupae formation from larvae, and the metamorphosis of pupae to the first generation of flies were faster in the TI group than the control group. Negative geotaxis and distance of the fly to its nearest neighbor are parameters of behavioral assessment in fruit flies. Negative geotaxis significantly decreased in the first generation of both male (p = 0.0021) and female (p = 0.0426) flies. The distance between the first generation of flies to its nearest neighbor was shorter in both male and female offspring flies in the TI group as compared to control group flies. These results indicate that TI to the female flies affected the development of larvae and resulted in early delivery, impaired social interaction and behavioral alterations in the offspring.